Use of a Dry Surgical Simulator Improves Orthopaedic Residents' Competency and Technical Skills for Arthroscopic Rotator Cuff Repair - Claudio Chillemi, M.D; Domenico Paolicelli, M.D; Carlo Paglialunga, M.D; Gennaro Campopiano, M.D; Mario Guerrisi, M.D; Riccardo Proietti, M.D; Cristina Carnevali, M.D (Elsevier, 2022)
Purpose: To evaluate whether an anatomic dry shoulder Dexter training model surgical simulator would be effective in augmenting orthopaedic residents' skills for arthroscopic rotator cuff repair. Methods: Nine residents, enrolled for this prospective study, watched a video presentation about transosseus equivalent (TOE) double-row, rotator cuff repair technique, repeating the aforementioned technique twice on the simulator. The time to complete all steps to final repair, as well as the quality of the final repair, were measured. Results: The data for repair completion time showed a statistically significant difference in the total duration time of performing the procedure, when comparing the timing in tests 1 and 2, demonstrating a reduced operative time. The qualitative data collected show an increase in the final score in 100% (9 out of 9) of the participants between the first and second tests, with an improvement in the average score of 16.4% (3.22 points with a standard deviation of 2.64). Hence, there is a statistically significant difference (P = .006) between the total scores obtained by the participants at the end of tests 1 and 2, presenting an improvement of the quality score, shifting from the first (average score 19.7) to the second (average score 22.9) test. Conclusion: The dry simulator may be a valuable device to improve arthroscopic technical skills. This improvement was observed both in the resulting reduced operative time required to carry out the surgical procedure and the increased quality score (established to evaluate the quality of the required tasks). Clinical Relevance: In order to provide as many training opportunities as possible, an arthroscopy simulator could be used to supplement clinical arthroscopy skills training for orthopaedic residents.